Clients' Perspective for Quality of Services at One of the Urban Primary Health Centres (U-PHC) at Municipal Corporation Area in One of the cities of Western India - Dharati Jani; Rashmi Sharma (Indian Association of Preventive and Social Medicine, 2022)
Introduction: Client satisfaction surveys are central to quality improvement at health facility. It helps in identifying areas of low satisfaction and steps to maximize patient satisfaction. Objectives: To assess client satisfaction towards services at Out Patient Department (OPD) of at an U-PHC under Ahmedabad Municipal Corporation (AMC), identify areas of low satisfaction and suggest feasible remedial measures for improvement. Method: Out of 74 U PHCs under AMC, 1 was selected through simple random sampling. Quality of care was evaluated through client's feedback which was gathered through 10 check points (on structure, process and outcome) developed by state level quality team. Responses of 300 adult (> 18 years) subjects and their mean ± standard deviation scores were calculated. These subjects were selected consecutively @ 25 cases (new cases who came first and were willing) on every 2nd and 4th Mondays for 6 months (Sep 2019 - Feb 2020). Results: While availability of drugs was perceived as very satisfying that of investigations was relatively an area of concern. Overall, only 1 client rated the services as average while all rest (99.6%) rated services as very good to excellent. Conclusion: Quality of services at this U PHC was good to excellent and had wider acceptability among its client.